Cartographic and remote-sensing data as a source of landscape ecological information on the Poznań metropolitan area - Kijowski, Andrzej; Kubiak, Jarosław; Ławniczak, Radzym; Mania, Wojciech (My University, 2010)
This paper characterises the system of organisation and access to spatial information in Poland based on the example of the Poznań metropolitan area. It describes the available cartographic resources, both topographic (general) and thematic. Particular attention was paid to remote sensing, being the source of the most current and nongeneralised information on geographic space. As a result of the implementation of the INSPIRE directive, activities aimed at integrating and sharing spatial data in a digital form were intensified. A practical outcome of the above is presented in the article published at Geoportal (www.geoportal.gov.pl). The final part of this paper shows the current applications and requirements concerning the use of spatial data in the modern management of a metropolitan area.
Keywords: Poznań metropolitan area; remote sensing; cartography; spatial data; GIS